Pembatalan Perjanjian Pengikatan Jual Beli Terkait Pembayaran Objek Jual Beli (Studi Putusan Nomor 27/Pdt.G/2019/PN Krs) - Tania Novebriani lase; hasim purba; mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
The Sale and Purchase Binding Agreement (PPJB) as an authentic deed has perfect evidentiary power based on Article 1868 of the Civil Code. Decision Number 27/Pdt.G/2019/PN Krs canceled the PPJB due to the buyer's default in failing to fulfill payment obligations. Cancellation of the deed results in the restoration of the parties' rights to their original position in accordance with Article 1451 of the Civil Code. However, there was an error by the Judge for not considering Article 16 paragraph (1) letter m of the Notary Position Law regarding the requirement of 2 witnesses in deed preparation, thus creating legal uncertainty regarding the evidentiary power of PPJB as an authentic deed.